Determinants of health expenditures: income level countries analysis - Azwardi Azwardi; Sukanto Sukanto; Nazeli Adnan (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
A global health phenomenon, in particular, there is a significant difference between health spending in developed and developing countries. This study focuses on modeling health expenditures in short-term and long-term schemes in three categories of countries: low-income countries, moderate-income, and high income from 2000 to 2019. The health expenditure scheme is analyzed using the panel data regression approach as a model of determinants of health expenditures. The results showed relatively significant differences between the determinants of health expenditure variables, including populations variable in low-middle-income countries. The positive and significant influences on middle-income countries, whereas high-income countries have a negative and significant influence. As for the overall GDP variable, low-income, lower-middle, and advanced countries negatively and significantly influence health care. For middle-income countries have a positive and significant influence on health spending.